Spatial analysis of the functional and spatial competencies of basic education schools in the municipal branch of Al-Zarouq municipality of Misurata study in the geography of educational services - Jahan, Mustafa; Al-Ssol, Abo-Baker ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2020)
The paper dealt with the functional and spatial competence of basic education schools spread over the geographical area within the urban area of ​​AL- Zaruq Municipal Branch, and its impact on the level of services provided by these institutions and their ability to meet the requirements of the region, which is an urban center of great importance. Because it is close to the city center of Misurata to the city center of Misurata, its population density and the diversity of its economic activities, the study also showed the relationship between the increase in the size of the population and the number of schools and measuring the extent of their spatial and functional efficiency. The research relied on analyzing the spatial distribution of schools on the tools of spatial analysis in Gis and using population and spatial criteria as criteria for increase and decrease in the number of schools compared to the population. The research found that there were deficiencies in the number of schools and that they adopted the random pattern caused by the failure to follow the correct planning standards